Digital Literature Culture For the Millenial Generation in the World of Education - Muryati, Afri; agustin, wulan dwi; Putri, Fauziah Rizky (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
This study discusses digital literacy specifically in the millennial generation and the world of education where literacy itself is defined as the individual's ability to manage and understand information in carrying out a reading or writing activity. And it can also be said that literacy is a person's skills and abilities in reading, writing, and solving problems in everyday life. With increasingly sophisticated technology, especially in the digital world, many people prefer to use simple things by utilizing digital technology. Therefore, there are many other ways or methods to develop literacy, especially in the world of education, namely with digital literacy. which in this way can certainly greatly facilitate people to develop literacy, especially in the world of education, not only digital literacy, but also many other developments to facilitate teaching and learning activities using digital technology, namely the existence of digital libraries and also e-learning, which means a digital library is a system that has various services and information objects that support access to information objects through digital devices. While e-learning itself is an activity in learning that utilizes networks such as the Internet, LAN, WAN as a method of delivery, interaction, and facilitation and is supported by many other forms of learning servicesKeywords: literacy, digital, education DOI: http://dx.doi.org/10.23960/jpvti.v3.i2.202102